Managing uncertainty in movement knowledge for environmental decisions. Issue 3 (3rd December 2018) - Smith, Annabel L.; Kujala, Heini; Lahoz‐Monfort, José J.; Guja, Lydia K.; Burns, Emma L.; Nathan, Ran; Alacs, Erika; Barton, Philip S.; Bau, Sana; Driscoll, Don A.; Lentini, Pia E.; Mortelliti, Alessio; et al.
Abstract: Species' movements affect their response to environmental change but movement knowledge is often highly uncertain. We now have well‐established methods to integrate movement knowledge into conservation practice but still lack a framework to deal with uncertainty in movement knowledge for environmental decisions. We provide a framework that distinguishes two dimensions of species' movement that are heavily influenced by uncertainty: knowledge about movement and relevance of movement to environmental decisions. Management decisions can be informed by their position in this knowledge‐relevance space. We then outline a framework to support decisions around (1) increasing understanding of the relevance of movement knowledge, (2) increasing robustness of decisions to uncertainties and (3) improving knowledge on species' movement. Our decision‐support framework provides guidance for managing movement‐related uncertainty in systematic conservation planning, agri‐environment schemes, habitat restoration and international biodiversity policy. It caters to different resource levels (time and funding) so that species' movement knowledge can be more effectively integrated into environmental decisions.